Efektivitas Pelayanan Pendaftaran Diklat Berbasis AIRIS (Aplication Integrated Registration System) terhadap Kepuasan Peserta Diklat di Poltekpel Banten - Abdul Hamid Arribathi; Sriyono Sriyono (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital transformation in public services is an effort to improve efficiency, transparency, and quality of service. Banten Maritime Polytechnic (Poltekpel Banten) as a Public Service Agency (BLU) has implemented the AIRIS (Application Integrated Registration System) online registration system to support the recruitment process of training participants, both new training participants and those upgrading their diplomas or certificates of seafaring skills training. The research method used is descriptive quantitative with data collection through questionnaires distributed to training participants who have used the AIRIS system. Data analysis was carried out using a Likert scale approach and effectiveness tests based on indicators of system quality, information quality, and service quality. The results of the study show that the implementation of AIRIS has a positive impact on increasing the efficiency of the registration process, data transparency, and ease of access to information for participants. Most respondents expressed a high level of satisfaction with the ease of use and speed of service provided by the system. However, several technical challenges, such as network disruptions and limited user guides for new users, were still encountered. Overall, AIRIS was deemed effective in improving the quality of training registration services and contributing to increased participant satisfaction. Therefore, it is recommended that it be further developed through feature optimization and increased digital infrastructure capacity.